Evolutionary biology of lichen symbioses. Issue 5 (18th March 2022) - Spribille, Toby; Resl, Philipp; Stanton, Daniel E.; Tagirdzhanova, Gulnara
Summary: Lichens are the symbiotic outcomes of open, interspecies relationships, central to which are a fungus and a phototroph, typically an alga and/or cyanobacterium. The evolutionary processes that led to the global success of lichens are poorly understood. In this review, we explore the goods and services exchange between fungus and phototroph and how this propelled the success of both symbiont and symbiosis. Lichen fungal symbionts count among the only filamentous fungi that expose most of their mycelium to an aerial environment. Phototrophs export carbohydrates to the fungus, which converts them to specific polyols. Experimental evidence suggests that polyols are not only growth and respiratory substrates but also play a role in anhydrobiosis, the capacity to survive desiccation. We propose that this dual functionality is pivotal to the evolution of fungal symbionts, enabling persistence in environments otherwise hostile to fungi while simultaneously imposing costs on growth. Phototrophs, in turn, benefit from fungal protection from herbivory and light stress, while appearing to exert leverage over fungal sex and morphogenesis. Combined with the recently recognized habit of symbionts to occur in multiple symbioses, this creates the conditions for a multiplayer marketplace of rewards and penalties that could drive symbiont selection and lichen diversification. Abstract : See also the Commentary on this article by Kranner et al., 234 : 1541–1543 .